2017
DOI: 10.16965/ijpr.2017.191
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Find the Effect of Stabilization and Extension Exercises on Patients With Sub Acute Non-Specific Low Back Pain

Abstract: Aim: The purpose of the study is to find out the effectiveness of lumbar stabilization exercises and extension exercises in patients with sub acute non-specific low back pain. Materials and Methods: 30 patients with non specific sub acute low back pain and no clinical signs suggesting spinal instability were recruited (Stabilization training: n=15; Mc Kenzies back extension: n=15). Both groups received 6 weeks of exercises intervention. Outcome measure were pain (Visual analog scale), range of motion (inch tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…These consequences are severe and may lead to a negative economic impact, which includes an increased absenteeism from workplace and loss of productiveness 4 . Nevertheless, most episodes of mechanical LBP have a favorable prognosis but the recurrence of pain within a year is common 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These consequences are severe and may lead to a negative economic impact, which includes an increased absenteeism from workplace and loss of productiveness 4 . Nevertheless, most episodes of mechanical LBP have a favorable prognosis but the recurrence of pain within a year is common 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies estimated that workers involved in healthcare comprises of physical and occupational therapists have predominant risk in developing LBP, either mechanical or specific due to prolonged sitting, standing, stooping and repetitive low and high risks lifting activities due to nature of their daily activities [1][2][3][4][5] . It was also concluded that occupational therapists have substantial degrees of musculoskeletal pain and work-related disorders due to the physical demand of their role in health care 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations